Somatostatin receptors (SSTR1-5) on inhibitory interneurons in the barrel cortex - Lukomska, Agnieszka (Brain Struct Funct, 2019)
Inhibitory interneurons in the cerebral cortex contain specific proteins or peptides characteristic for a certain interneuron subtype. In mice, three biochemical markers constitute non-overlapping interneuron populations, which account for 80–90% of all inhibitory cells. These interneurons express parvalbumin (PV), somatostatin (SST), or vasoactive intestinal peptide (VIP). SST is not only a marker of a specific interneuron subtype, but also an important neuropeptide that participates in numerous biochemical and signalling pathways in the brain via somatostatin receptors (SSTR1-5). In the nervous system, SST acts as a neuromodulator and neurotransmitter affecting, among others, memory, learning, and mood. In the sensory cortex, the co-localisation of GABA and SST is found in approximately 30% of interneurons. Considering the importance of interactions between inhibitory interneurons in cortical plasticity and the possible GABA and SST co-release, it seems important to investigate the localisation of different SSTRs on cortical interneurons. Here, we examined the distribution of SSTR1-5 on barrel cortex interneurons containing PV, SST, or VIP. Immunofluorescent staining using specific antibodies was performed on brain sections from transgenic mice that expressed red fluorescence in one specific interneuron subtype (PV-Ai14, SST-Ai14, and VIP-Ai14 mice). SSTRs expression on PV, SST, and VIP interneurons varied among the cortical layers and we found two patterns of SSTRs distribution in L4 of barrel cortex. We also demonstrated that, in contrast to other interneurons, PV cells did not express SSTR2, but expressed other SSTRs. SST interneurons, which were not found to make chemical synapses among themselves, expressed all five SSTR subtypes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00429-019-02011-7) contains supplementary material, which is available to authorized users.